ECONOMIC IMPROVEMENT OF RURAL BPL HOUSEHOLDS THROUGH SHGS: A STUDY AT AURANGABAD DISTRICT OF MAHARASHTRA - Chatterjee, Shankar (International Journal of Research -GRANTHAALAYAH, 2019)
This study was carried out among the members of self-help groups (SHGs) at Aurangabad District of Maharashtra in the Month of March 2019. Altogether, two SHGs located in two different areas along with the few members of SHGs were contacted to get an idea about the functioning of self-help group (SHG) in the district as well as earning (income) of members after joining in the SHG. The SHGs were part of earlier Swarnajayanthi Gram Swarojgar Yojana (SGSY), a self-employment scheme sponsored under Ministry of Rural Development, Government of India. In view of this few lines about SGSY and its progress are presented here for the benefit of readers. So, the study is based on both primary and secondary data.